1999
DOI: 10.1021/om990668q
|View full text |Cite
|
Sign up to set email alerts
|

The Titanium(III)- and Samarium(II)-Promoted Rearrangement of a Vinylcyclobutene 1,2-Diester to 1,2-, 1,3-, and 1,4-Phthalates

Abstract: We have discovered a novel rearrangement of a vinylcyclobutene 1,2-diester into a mixture of 1,2-, 1,3-, and 1,4-phthalates. On the basis of deuterium labeling studies, a mechanism for this rearrangement is proposed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…As to the composition of Met−Cp 2 TiCl 2 solutions, the distribution of Ti III species in a 0.5 mM solution, for example, will be 0.22 mM Cp 2 TiCl and 0.14 mM (Cp 2 TiCl) 2 , while the corresponding numbers for a 100 mM solution will be 4 and 48 mM. Depending on the exact reaction conditions (catalytic or stoichiometric), either of the two species may thus be the dominant one. In our previous study we showed that Cp 2 TiCl 2 - could be generated from Cp 2 TiCl and free Cl - with a relatively large formation equilibrium constant of 10 4 M -1 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As to the composition of Met−Cp 2 TiCl 2 solutions, the distribution of Ti III species in a 0.5 mM solution, for example, will be 0.22 mM Cp 2 TiCl and 0.14 mM (Cp 2 TiCl) 2 , while the corresponding numbers for a 100 mM solution will be 4 and 48 mM. Depending on the exact reaction conditions (catalytic or stoichiometric), either of the two species may thus be the dominant one. In our previous study we showed that Cp 2 TiCl 2 - could be generated from Cp 2 TiCl and free Cl - with a relatively large formation equilibrium constant of 10 4 M -1 .…”
Section: Resultsmentioning
confidence: 99%
“…Low-valent metal complexes employed as single electron transferring agents are important reagents for promoting organic synthetic transformations . One of these, which has become increasingly popular over the past few years, is bis(cyclopentadienyl)titanium chloride (Cp 2 TiCl), promoting highly diastereoselective pinacol coupling reactions, epoxide openings to alkyl radicals, reductions of alkyl halides such as glycosyl bromides 4 and vic -dibromides, Reformatsky additions, and others. The generation of the trivalent titanium species in tetrahydrofuran (THF) may be achieved by direct substitution of two of the chlorides in TiCl 3 with metalated cyclopentadiene 10 or by simple reduction of Cp 2 TiCl 2 with metals such as zinc, aluminum, and manganese . Cp 2 TiCl has likewise been reported to be obtained after electrode reduction of Cp 2 TiCl 2 …”
Section: Introductionmentioning
confidence: 99%
“…The chemistry is also promoted by other noteworthy transformations, involving reduction to Cp 2 Ti III and Cp 2 Ti II species, loss of the ring to give CpTiCl 3 , and replacement of halogen by other unidate ligands . Furthermore, the reduction of Cp 2 TiCl 2 with Al, Mn, and Zn in tetrahydrofuran leads to the dimeric (Cp 2 TiCl) 2 active Nugent’s reagent for the highly diastereoselective pinacol coupling reaction of aldehydes, epoxide openings to alkyl radicals, and other reactions. In contrast, the dissolution of Cp 2 TiCl 2 in water produces a low pH, in which the chloride ligands are replaced by H 2 O and OH − ligands, and results in protonation and loss of the Cp groups and the formation of insoluble Ti oxo species . Moreover, titanocene dichloride showed great promise as an effective antitumor agent .…”
Section: Introductionmentioning
confidence: 99%
“…1 Such reagents have found widespread use in synthetic organic chemistry, promoting highly diastereoselective pinacol coupling reactions, 2 epoxide openings to alkyl radicals, 3 reductions of alkyl halides such as glycosyl bromides 4 and vic-dibromides, 5 Reformatsky additions, 6 and others. [7][8][9] Furthermore, interesting catalytic versions of some of the synthetic transformations have been developed, whereby Ti III is regenerated in situ after electron transfer to the substrate. 1 Despite their importance, information concerning the nature and reactivity of the Ti III species formed in Met-Cp 2 TiCl 2 solutions has been lacking.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, metal-reduced titanocene dichloride, Met-Cp 2 TiCl 2 (Met = Zn, Mn, and Al), has found interesting applications as selective single-electron-donating reagents, where stoichiometric amounts of the metal are employed to generate Ti III -based species from reduction of Cp 2 TiCl 2 . Such reagents have found widespread use in synthetic organic chemistry, promoting highly diastereoselective pinacol coupling reactions, epoxide openings to alkyl radicals, reductions of alkyl halides such as glycosyl bromides 4 and vic -dibromides, Reformatsky additions, and others. Furthermore, interesting catalytic versions of some of the synthetic transformations have been developed, whereby Ti III is regenerated in situ after electron transfer to the substrate . Despite their importance, information concerning the nature and reactivity of the Ti III species formed in Met-Cp 2 TiCl 2 solutions has been lacking.…”
Section: Introductionmentioning
confidence: 99%